William Cogswell papers - Cogswell, William, 1838-1895.
TLsS (1893 September 15 and December 23; Washington, D.C.) from Cogswell to William A. Swan, Salem, Mass., pertaining primarily to the silver question and other matters before Congress, Grover Cleveland and the Democratic Party, and local politics in Salem, Mass. Also includes an illustration of Cogswell on a plate removed from a book.
U.S. representative, Union army officer, and lawyer from Massachusetts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cleveland, Grover, -- 1837-1908.; Swan, William A. -- Correspondence; Democratic Party (U.S.); Silver question; Salem (Mass.) -- Politics and government; United States -- Politics and government -- 1889-1893.; Army officers; Lawyers; Representatives, U.S. Congress -- Massachusetts